PENGOPTIMALAN MARKA TERHADAP KETERTIBAN PENGGUNAAN GROUND SUPPORT EQUIPMENT DI TERMINAL KARGO BANDAR UDARA SULTAN AJI MUHAMMAD SULAIMAN SEPINGGAN BALIKPAPAN - Maulana Yusuf; Abdul Mu’ti Sazali; Wiwid Suryono (Prosiding SNITP (Seminar Nasional Inovasi Teknologi Penerbangan))
This study discusses the optimization of markers in the terminal of Sultan Aji Muhammad Sulaiman Sepinggan Airport Balikpapan. The research of this topic is based on field observations. The observations explain that the condition of the markers in the cargo terminal of Sultan Aji Muhammad Sepinggan Airport Balikpapan. (SAMS) is not used as functioned. This research aims to create order in the cargo terminal of SAMS Sepinggan Balikpapan airport, especially the use of Ground Support Equpment (GSE). Data collection techniques used are observation, interview, literature review, and documentation.Data analysis uses Miles and Huberman theory with three steps, namely data reduction, data presentation, and conclusion drawing. The result of the study is the condition of the markers inside the cargo terminal sams airport is not used according to its function because the markers have faded and the lack of socialization of the use of markers to the airline. Therefore, there needs to be procurement and renewal of markers in the Area build up and breakdown so that the laying and use of GSE can be organized in the area of Cargo Terminal Sultan Aji Muhammad Sulaiman Sepinggan Airport Balikpapan